Gender Relationship Patterns in the Families of Female Farm Workers in Enrekang Regency: Sociological Analysis - Suparman, Suparman; Kasnawi, Tahir; Syukur, Muhammad; Kamaruddin, Syamsu A (International Journal of Educational Narratives, 2024)
Background. Gender relations in farm laborer families are one important aspect that reflects the social and economic dynamics in rural Indonesia, especially in Enrekang Regency. Female farm laborers play dual roles, both in agricultural work and domestic responsibilities. However, their contributions are often not recognized equally in a society that is still patriarchal. Purpose. This study aims to understand the form of gender relations in female farm laborer families in Baraka District, and to analyze its impact on family welfare. Method. The method used in this study is a descriptive approach. Data collection was carried out through in-depth interview techniques with 101 female farm laborers, 61 husbands, 11 landowners, and 9 community leaders and local government officials, who were selected purposively. Participatory observation was also conducted to understand the daily dynamics of women in farm laborer families, especially related to the division of labor, access to resources, and decision making. In addition, document analysis was used to complement the information obtained from interviews and observations, in order to obtain a more comprehensive picture of the social and economic context in Baraka District. Results. The results of the study show that the division of labor is still dominated by patriarchal norms, where women have to play dual roles as workers in the fields and housekeepers. Women’s access to resources, such as land and credit, is also very limited, hampering their ability to contribute optimally to agriculture. Strategic decisions in the family are generally made by men, while women are only involved in operational decisions. In addition, there is inequality in wages between female and male farm workers, even though the work done is the same. Conclusion. The conclusion of this study is that unequal gender relations hinder the welfare of women and farm laborer families as a whole. However, there is hope for change through education and empowerment of women, as well as more inclusive policy support from the government. Collaborative efforts are needed to create better gender equality in the rural agricultural sector.